National Microfinance Development Strategy - Central Bank of Nigeria (2012)
The National Microfinance Development Strategy (NMDS) is aimed at providing a blue print that will enable stakeholders in the microfinance industry to efficiently and effectively perform their roles and responsibilities and further improve the access level to financial services
osc 30/08/2021
Arch
Keywords: Microfinance; Nigeria